Estimulación de lenguaje para prevenir los trastornos de lectura y escritura en los niños y niñas de 3 a 4 años en el centro de educación inicial María Montessori provincia de Cotopaxi, cantón Latacunga, parroquia La Matriz en el año lectivo 2014-2015 - Toapanta Tipán, Mónica Alexandra (2015)
In 2011, the new law of in our country established three levels of education: Initial, Basic General and secondary Education; My research is focused in initial education with children between three to five years who intends to carry out different types of activities prior to basic education; with the goal of encouraging language and prevent disorders reading and writing, which are one of the most recurrent problems that arise today in children. In the first chapter deals with aspects related to the stimulation of language Nowadays, the most frequent learning problem in the children are reading and writing disabilities, so many research have been developed in order to prevent and trait these difficulties. Therefore, the present research contains aspects related with language stimulation to support the language acquisition specifically to improve reading and writing skills. The education is a necessity, for this reason is significant that teachers and parents work together in properly and strategic ways to stimulate the language acquisition which will be a fundamental base to develop the basic aspects in the growth of children, applying different techniques of research contributed to get specific data which were analyzed and processed to get results that inspired to create a guide with activities that allow as to reinforce the language acquisition in children. The guide as a didactic resource for teachers contains activities to apply in the classroom which will motivate the children introducing them to meaningful learning. The main goal of this resource is encouraging children to improve the reading and writing skills in a fun way; playing, creating and imaging as well as, supporting the development the fine and gross motor skills.